Utilização de levedura de Tórula (Candida utilis) na alimentação de fases jovens de tilápia do Nilo: respostas ao desempenho produtivo e alterações histológicas - Vogel, Lucas Fabrício (2019)
Yeasts are an important group of microorganisms used as additives in animal nutrition. In this work, the parameters of productive performance and intestinal histological changes of young Nile tilapia phases were evaluated in two feeding trials with diets containing increasing levels of full-blown yeast (Candida utilis). For the first test with medium weight fish (0.027 ± 0.01g) and for the second fish test medium weight (0.730 ± 0.029g). Six test diets were elaborated, being a basal diet without yeasts (CO), four diets with increasing levels of inclusion of full yeast of Torula (LT) (Candida utilis), (0.75, 1.50, 2.25 and 3.00% Cinergis®). And a positive control test diet using brewer's yeast (LC) (Saccharomyces cerevisiae) at the inclusion level (3.0%) to be compared to the higher inclusion level of Torula yeast. The performance data, morphometry of histological samples were evaluated for normality and homoscedasticity and submitted to analysis of variance (ANOVA), at the 5% level of significance. For the first trial, significant effects (p <0.05) of fish feed were observed with inclusion of turkey yeast at the 3.0% level under the parameters of final weight and weight gain in relation to the basal diet without inclusion of yeasts. There was no significant difference in final weight and weight gain at lower levels of inclusion of torula yeast (0.75, 1.50, 2.25%). In the second trial, no significant effects (p> 0.05) were observed for the inclusion of torula yeast at different levels and brewer's yeast under the productive parameters. For the second test, only alterations in the morphometric evaluation of intestinal samples with medium weight animals (0.730 ± 0.029 g) at the time of intestinal villi were observed in the treatment with a higher level of inclusion of torula yeast (Candida utilis).